Persepsi pengguna terhadap reka bentuk dan warna yang digunakan pada logo - Nurul Fazzuen, binti Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study is to identify whether there are different of consumers perceptions about design on logos between typography and symbols and to identify whether there are differences between the sexes of favorite colors. A total of 200 respondents were used as samples and the data was analyzed. Descriptive analysis was used to analyze the frequency of demographic classification. In addition, analysis cross tabulation was used to find out the favorite colors based on genders. Based on the discovery notice that there are differences of perception logo design between typography and symbols and differences favorite color based on genders. This thesis was the beginning conducted by researches and hopes will benefit many people especially to designer of logos industrial.